Link Layer Priority Management Techniques for Supporting Real Time Traffic in CDMA Based Wireless Mesh Networks - Alsabaan, Maazen (University of Waterloo, 2007)
With the recent advances in the development of wireless communication networks, Wireless Mesh Networks (WMNs) have been receiving considerable research interests in recent years. Many challenges need to be addressed for successful WMN deployment. One of the fundamental challenges is the need to support integrated services and provision different Quality of Service (QoS) for various applications. In order to allow differentiated services, Medium Access Control (MAC) has to provide priority management techniques at the link layer. In Code Division Multiple Access (CDMA) based WMNs, the interference phenomenon and the simultaneous transmissions must be considered. We propose two priority schemes for a distributed CDMA-based MAC WMNs. We take into account interference, multiple services, QoS requirements for each type of traffic, and the simultaneous transmission in CDMA. The first priority scheme is within a node. Each node has independent queues for each traffic class. According to QoS requirements, the queue that should be served first is determined. The second priority scheme is among neighbour nodes. It is proposed for possible multiple simultaneous transmissions with CDMA. This scheme gives a higher chance of correct transmission to high priority traffic than low priority traffic. In addition, we propose to use an adaptive spreading gain and a frame structure to achieve high resource utilization. Simulation results demonstrate that the proposed schemes can achieve effective QoS guarantee.
Keywords: Electrical and Computer Engineering